Development of Computerized Maintenance Management System for Manufacturing Factory - Mohd Rofi, Muhammad Alauddin Shah; Kasim, Shahreen (Applied Information Technology And Computer Science, 2022)
Every manufacturing factory has their own technicians to take care their own equipment or asset, so by using Computerized Maintenance Management System (CMMS), the company can centralize all the technicians work order, as well as asset management in computer. The project is studied to develop CMMS for manufacturing factory, which is Synapse is the stakeholder. The project is developed using agile method to plan, analyze, design, implement, and test, where several meetings were conducted with the client. A prototype has been developed to get a better picture on how the system will flow and work. The next goal is to develop the system as planned with the client.